The Rise of Multi-Cloud Architecture: A Technical Deep Dive - Sachin Kumar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Multi-cloud architecture has emerged as a transformative approach in modern enterprise computing, fundamentally changing how organizations deploy, manage, and scale their digital infrastructure. This technical article examines the evolution of multi-cloud strategies, exploring the key drivers behind their adoption and the enabling technologies that make them possible. The article investigates the critical role of containerization and orchestration in achieving workload portability, while also analyzing the impact of service discovery, networking solutions, and infrastructure as code practices. The article further explores emerging trends in financial management, networking advancements, and compliance frameworks that are shaping the future of multi-cloud implementations. Through comprehensive analysis, this article demonstrates how multi-cloud architectures enable organizations to enhance operational efficiency, improve security posture, and maintain regulatory compliance while avoiding vendor lock-in.